Increased Organic Fertilizer and Reduced Chemical Fertilizer Increased Fungal Diversity and the Abundance of Beneficial Fungi on the Grape Berry Surface in Arid Areas - Wu, Linnan; Li, Zhiqiang; Zhao, Fengyun; Zhao, Benzhou; Phillip, Fesobi Olumide; Feng, Jianrong; Liu, Huaifeng; Yu, Kun (Frontiers in Microbiology, 2021)
Fertilizer practices can significantly impact the fruit quality and microbial diversity of the orchards. The fungi on the surface of fruits are essential for fruit storability and safety. However, it is not clear whether fertilization affects the fungal diversity and community structure on the surface of grape berries. Here, grape quality and the fungal diversity on the surface of grapes harvested from three fertilizer treatments were analyzed shortly after grape picking (T0) and following 8 days of storage (T1). The study involved three treatments: (1) common chemical fertilizer for two years (CH), (2) increased organic fertilizer and reduced chemical fertilizer for one year (A.O), and (3) increased organic fertilizer and reduced chemical fertilizer for two years (B.O). The application of increased organic fertilizer and reduced chemical fertilizer increased the soluble solids content of the grape berries and decreased the pH of the grape juice. A total of 827,947 high-quality fungal sequences were recovered and assigned to 527 operational taxonomic units. Members of the Ascomycota phylum were dominant in all samples and accounted for 94.41% of the total number of detected sequences, followed by the Basidiomycota (5.05%), and unidentified fungi (0.54%). Alpha and beta diversity analyses revealed significantly different fungal populations in the three fertilizer treatments over the two time periods. The fungal diversity and richness on the grape berry surface in the B.O and A.O treatments were higher than those in the CH treatment. Among the detected fungi, the B.O treatments were mainly Pichia, Aureobasidium and Candida genera, while the CH treatments were Botrytis, Aspergillus and Penicillium. Moreover, significant differences were revealed between the two assessment times (T0 and T1). The samples from the T0 timepoint had higher fungal richness and diversity than the samples from T1 timepoint. Increasing organic fertilizer usage in grape management could improve grape quality and went on to increase the fungal diversity, as well as the relative abundance of beneficial fungi on grape berry surfaces. The correlation analysis suggested that the pH of the grape juice was significantly negatively correlated with fungal diversity parameters.